Toward holistic tension- or compression-biased structural designs using topology optimization. (15th November 2019) - Smarslik, Mario; Ahrens, Mark Alexander; Mark, Peter
Highlights: Topology optimization proves to be a viable multi-level structural design tool. Incorporation of tension and compression preferences is the method's key benefit. The enhancement enables a quick assessment of structures on local and global scales. Optimization-based strut and tie models yield improved reinforced concrete designs. Abstract: The efficiency of a structural design relies considerably on the knowledge and experience of its design engineer. It is critical to choose the proper structural system, cross-sections, and materials as these elements significantly influence the design's performance. Establishing computational methods that support the engineer in the design process and facilitate more objective solutions therefore represents an important step in creating proficient structural designs. In this paper, a novel approach is introduced to generate topology optimization results with an intended bias toward tension or compression for practical application in structural engineering. The results are deduced from the example of continuum elements and extended to cover truss topology optimization – assuming a linear-elastic, isotropic material model – in addition to combined truss–continuum topology optimization with bilinear, orthotropic material behavior. The effects of creating such solutions are analyzed at a simple theoretical problem. For the purposes of practically designing reinforced concrete structures, the preferable scope of application of each of the three methods is evaluated. The benefit of creating biased solutions is demonstrated by assessing their structural performance, robustness, and overall suitability on both global (system) and local (cross-section) scales and by applying them to common problems in structural engineering.